The Mandate of the Church in the Apocalypse of John - Peters, Olutola K. (My University, 2002)
The Apocalypse of John has elicited a wide range of responses. Captivated by its bizarre imagery, obscure references, and mythopoetic discourse, some (especially in popular writings) have engaged in an almost endless discussion attempting to decode the symbols and set out the order of predicted events. Others, convinced that it was intended to serve a pastoral function among its original recipients (the churches of Asia Minor), have focused on the practical message of its letters and visions for the Church. The scholarly consensus, as demonstrated in recent literature on the Apocalypse, is that John (the author) is not only interested in revealing things that must soon take place (Rev 1:1), but also in identifying what the Church must be and do (cf. Revelation 2-3). However, while recent scholarship demonstrates this common understanding that the Church is of vital concern to the author of the Apocalypse, and that the Apocalypse contains various tasks and functions for its recipients, the field lacks a comprehensive and cohesive discussion of all that the Church is meant to be and do. As a contribution, then, this dissertation is a study of what constitute various tasks and responsibilities of the Church as mandated in the Apocalypse of John. Obviously, in literature that abounds on the Apocalypse, several attempts have been made to identify and discuss particular issues, themes, and motifs that point to the task and mandate of the Church. However, there has been no systematic and comprehensive effort to explore all that the Apocalypse of John considers to be the mandate of the Church, and to demonstrate how the various tasks relate to one another. One of the main concerns of this dissertation, then, is the investigation of a category that encompasses the various tasks of the Church in the Apocalypse of John. In light of the prominence of the "witness" terminology in the Apocalypse of John and the dominance of the mandate to witness in other New Testament writings, this dissertation explores the possibility that the primary mandate of the Church in the Apocalypse of John is to maintain the "witness of Jesus" (ἡ μαρτυρία) , and it also examines whether the various tasks of the Church found in the Apocalypse are intended to converge under the mandate of the Church to maintain the "witness of Jesus." Furthermore, as a contribution to the μαρτυρία debate, an attempt has been made in this dissertation to draw attention to evidence that the "witness" terminology in the Apocalypse of John functions in more ways than are discussed and debated in scholarship. In terms of procedure and methodology, this dissertation examines various scholarly works that treat particular tasks and functions of the Church in the Apocalypse of John. However, in exploring the possibility that the various tasks and functions of the Church converge under mandate to maintain the "witness of Jesus," it focuses mainly on primary literature, the Apocalypse of John. It examines all the implicit and explicit references to the mandate of the Church in the Apocalypse of John and also explores the possibility that the author uses the phrase "the witness of Jesus" (ἡ μαρτυρία 'Iησοv) as an umbrella expression for various aspects of the Church's mandate. For structure, the introduction outlines the task of this dissertation and presents a summary of the "state of teh question" in contemporary scholarship. The first chapter provides a survey of the Apocalypse, identifying the relevant texts and classifying the various functions of the Church that are discussed in this dissertation. Subsequent chapters are devoted to detailed discussions of the tasks and functions of the Church with a main focus on the tasks of worship, witness and repentance. Through these discussions the comprehensive and cohesive nature of the mandate of the Church in the Apocalypse is demonstrated. The extent to which the tasks and functions of the Church are both varied and unified is also made evident.
Keywords: Religion; Religion